COVID-19: A Devastating Pandemic - Punet Kumar; Md Iftekhar Ahmad; Sangam Singh (Tabriz University of Medical Sciences, 2020)
Coronavirus disease 2019 (COVID-19) is a pandemic that was first reported in December 2019 in Wuhan, China. The disease is caused by virus SARS-CoV2. SARS-CoV2 has emerged from the highly pathogenic coronavirus in humans after Middle East respiratory syndrome coronavirus (MERS-CoV) and severe acute respiratory syndrome coronavirus (SARS-CoV) in the twenty-first century. Special efforts and attention to protect or reduce the transmission need to be applied in susceptible populations comprising elderly people, children, and health care providers. Different countries have implemented extensive measures to reduce person-to-person transmission of COVID-19 to regulate the current outbreak. In our review article, we provided a brief introduction to SARS-CoV2 and mentioned current knowledge on molecular immune pathogenesis, diagnosis, and treatment of COVID-19. Our work will help in offering novel insight and potential therapeutic targets for combating the SARS-CoV2 infection. Based on the research articles, we systemically discussed the characteristics of COVID-19 and provided some future aspects in the field of research.